A fast and easy-to-learn technique for liver resection in a porcine model - Majlesara, Ali; Khajeh, Elias; Ghamarnejad, Omid; Soleymanzadeh Gharabaghi, Negin; Tinoush, Parham; Mohammadi, Sara; Saeedi, Mohammed al; Mehrabi, Arianeb; Golriz, Mohammad (The journal of international medical research, 2021)
ObjectiveDespite the recent advances in surgical techniques and perioperative care, liver resection (especially extended hepatectomy) is still a high-risk procedure with considerable morbidity and mortality. Experimental large animal models are the best option for studies in this regard. The present study was performed to present an easy-to-learn, fast, and multipurpose model of liver resection in a porcine model.MethodStepwise liver resections (resection of segments II/III, IVa/IVb, and VIII/IV) were performed in eight pigs with intraoperative monitoring of hemodynamic parameters. The technical aspects, tips, and tricks of this method are explained in detail.ResultsBased on the specific anatomical characteristics of the porcine liver, all resection types including segmental resection, hemihepatectomy, and extended hepatectomy could be performed in one animal in an easy-to-learn and fast technique. All animals were hemodynamically stable following stepwise liver resection.ConclusionStepwise liver resection using stapler in a porcine model is a fast and easy-to-learn method with which junior staff and research fellows can perform liver resection up to extended hepatectomy under stable conditions.
Gesehen am 01.06.2022